Protocol for evaluating iodine uptake and diffusion in sheep and pig meniscus tissue using contrast-enhanced micro-CT and UV-vis spectroscopy - Federica Orellana; Annapaola Parrilli (STAR Protocols)
Summary: Here, we present a protocol for evaluating iodine uptake and diffusion in sheep and pig meniscus tissue using contrast-enhanced micro-computed tomography (CT) and ultraviolet-visible (UV-vis) spectroscopy. We describe steps for sample fixation, a staining procedure with iodine-based contrast agents, and imaging using micro-CT. We then detail procedures for volumetric and radiodensity analyses, UV-vis spectroscopy, and data processing.For complete details on the use and execution of this protocol, please refer to Orellana et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.